Spreminjanje položaja učenca v Sloveniji v 20. stoletju - Mithans, Monika; Ivanuš Grmek, Milena (Revija za elementarno izobraževanje, 2012)
Changes in pupils' situation in Slovenia in the 20th century. Pupils situation is an important topic of pedagogical theory and practice in Slovenia and worldwide. During different periods, the views on pupils situation have changed, generally reflecting the spirit of the time in which they emerged. This article analyses the changes in pupils situation throughout the educational process of the 20th century, based on studying domestic and foreign literature. The analysis discovered that the first vital changes to the situation of pupils in Slovenia were recorded after the First World War, when the active role of pupils and their freedom of choice gained more importance. The Second World War interrupted the effort to improve pupils situation. Soon after the War, pedagogical theorists and practitioners called attention to the meaning of pupils role in class. There are numerous discussions on the significance of changing pupils status from being an object to being a subject of the educational work. The turning point in thinking about the changed pupils situation within the educational process was a paper by Iva Šegula, presented at the first pedagogical congress. She strived for self-activity of pupils in class and for their subjective role. The demands to improve pupils situation continued after Slovenia's independence and are still going on. But unfortunately it was discovered that in spite of continuous efforts by theorists and practitioners alike, pupils are too often mere listeners, not engaging sufficiently in class.
Keywords: pupil; pupil’s situation; learning activity; educational process; participation